DIVERSITY STUDY OF FRUIT PRODUCER PLANT IN NIAS ISLANDS - Yan Piter Basman Ziraluo; Markus Duha (Jurnal Inovasi Penelitian, 2020)
This study aims to identify the kinds of fruit-producing plants in the Nias Island area, describe the characteristics of the fruitproducing plants, describe the diversity of fruitproducing plants, and find out the cultivation techniques of fruit producing plants. This research is a descriptive qualitative research type. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques through three stages, namely data reduction, data presentation, and drawing conclusions / verification. From the results of the study there were 30 types of plants planted by people in the Nias Island area.